The β-NGF/TrkA Signalling Pathway Is Associated With the Production of Anti-Nucleoprotein IgG in Convalescent COVID-19 - Usai, Carla; Gibbons, Joseph M.; Pade, Corinna; Li, Wenhao; Jacobs, Sabina R. M.; McKnight, Áine; Kennedy, Patrick T. F.; Gill, Upkar S. (Frontiers in Immunology, 2022)
Background. The presentation of SARS-CoV-2 infection varies from asymptomatic to severe COVID. Similarly, high variability in the presence, titre and duration of specific antibodies has been reported. While some host factors determining these differences, such as age and ethnicity have been identified, the underlying molecular mechanisms underpinning these differences remain poorly defined. Methods. We analysed serum and PBMC from 17 subjects with a previous PCR confirmed SARS-CoV-2 infection and 10 unexposed volunteers following the first wave of the pandemic, in the UK. Anti-NP IgG and neutralising antibodies were measured, as well as a panel of infection and inflammation related cytokines. The virus-specific T cell response was determined by IFN-γ ELISPOT and flow cytometry after over-night incubation of PBMCs with pools of selected SARS-CoV-2 specific peptides. Results. Seven of 17 convalescent subjects had undetectable levels of anti-NP IgG, and a positive correlation was shown between anti-NP IgG levels and the titre of neutralising antibodies (IC50). In contrast, a discrepancy was noted between antibody levels and T cell IFN-γ production by ELISpot following stimulation with specific peptides. Among the analysed cytokines, β-NGF and IL-1α levels were significantly different between anti-NP positive and negative subjects, and only β-NGF significantly correlated with anti-NP positivity. Interestingly, CD4+ T cells of anti-NP negative subjects expressed lower amounts of the β-NGF-specific receptor TrkA. Conclusions. Our results suggest that the β-NGF/TrkA signalling pathway is associated with the production of anti-NP specific antibody in mild SARS-CoV-2 infection and the mechanistic regulation of this pathway in COVID-19 requires further investigation.